Identiti kemelayuan dalam pentadbiran Kedah, 1923-1941 - Noor Ain Mat Noor; Ahmad Kamal Ariffin Mohd Rus (Penerbit UKM, 2014)
This paper looks at the Malay identity adopted in the Kedah administration following the 1923 Anglo-Kedah Treaty. Among the main articles in the Treaty revolved around the use of Malay and the Jawi script as the official language and script, as well as other articles directly related to administration in Kedah. The 1923 Treaty included a number of conditions introduced by Tunku Ibrahim (Regent of Kedah) to the British, whereby all these conditions touched on Malay position in administration. By analysing each aspect of the treaty and the conditions, a number of questions are forwarded. First, did the Malay tongue and the Jawi script remain in use in the Kedah administration after the signing of the 1923 Treaty? Second, did the conditions that Tunku Ibrahim introduced include prioritising Malays in the filling in of positions in the Kedah administration? Overall, the 1923 Treaty did not negatively affect Malay dominance in administration. Malays still manage to maintain their Malay identity through the use of the Malay language and the Jawi script in matters of correspondence, official records and official documents. At the same time, the Kedah Malay identity was strengthened by Malay dominance in both central- and district-level administration.